Aggregative properties of red blood cells platelets in young cattle in the first 10 days of life - T A Belova; S Y Zavalishina; O V Nagornaya; I N Medvedev (RUDN Journal of Ecology and Life Safety, 2014)
Objective: to establish features erythrocyte and platelet at healthy calfs in a phase newborn. The animals every day during the newborn phase determined aggregation cells using light microscopy and Visual mikrometod aggregation platelets. The results may apply the fundamental research on the physiology of the uniform of the blood in mammals in the early stages of ontogenesis. Contained in the information you can use in veterinary practice in the examination and treatment of newborn calves.